2017
DOI: 10.1183/16000617.0045-2017
|View full text |Cite
|
Sign up to set email alerts
|

Immune checkpoints in chronic obstructive pulmonary disease

Abstract: Cell-mediated immune responses are vital to the body's defence against infection and play a key role in tumour immunity. T-cell activation and cytotoxic function is tightly regulated by a series of immune-regulatory receptor-ligand interactions or immune checkpoints. These controls limit immune-mediated damage, particularly in the context of chronic infection. However, prolonged signalling through these axes can lead to progressive loss of T-cell function, termed exhaustion.Understanding of the biology of chec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 57 publications
(55 reference statements)
0
28
0
Order By: Relevance
“…COPD features dysregulated immune checkpoint axes. 30 Relative to healthy subjects, patients with COPD show attenuated programmed death ligand 1 expression on alveolar macrophages in response to viral infections and elevated interferon-g release. 31 This milieu of immune dysregulation may predispose the chronically inflamed COPD lung to more frequent and higher grade pneumonitis.…”
mentioning
confidence: 99%
“…COPD features dysregulated immune checkpoint axes. 30 Relative to healthy subjects, patients with COPD show attenuated programmed death ligand 1 expression on alveolar macrophages in response to viral infections and elevated interferon-g release. 31 This milieu of immune dysregulation may predispose the chronically inflamed COPD lung to more frequent and higher grade pneumonitis.…”
mentioning
confidence: 99%
“…As immunotherapies can modulate T-cell response via inhibition of immune checkpoints, they may be of potential therapeutic value for COPD. There are emerging data suggesting a potential role of dysregulated immune checkpoints leading to excessive T cell response in COPD [103].…”
Section: Systemic Therapiesmentioning
confidence: 99%
“…The speed of the lymphatic flow is approximately 125 mL/h in a person at rest but can increase by a factor of 10 during active movements [12][13]. Another passive mechanism that can manage lymphatic flow is oxygen pressure, particularly at low gradients (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40); if the oxygen pressure is higher, the lymphatic flow slows down. Temperature can also influence the speed of the lymphatic flow; the function of the lymphatic system is optimal at temperatures ranging between 32°C and 37°C, and probably acts via extracellular osmotic changes.…”
Section: Review the Lymphatic Systemmentioning
confidence: 99%
“…Another signal of the constant activation of T lymphocytes and the generally inflammatory status is the reduction in function and quantity of some receptors. T lymphocytes have receptors known as "receptor programmed death" type 1 (PD1) which regulate the half-life of lymphocytes [36]. Studies have shown that the enlargement and neoformation of the lymphatic nodes and vessels reflect the severity of pathology in patients with COPD; there is a close relationship between COPD and pulmonary lymphatic system dysfunction [1,19,[37][38].…”
Section: How Does the Lymphatic System Behave In The Presence Of Copd?mentioning
confidence: 99%